2005
DOI: 10.1111/j.1348-0421.2005.tb03698.x
|View full text |Cite
|
Sign up to set email alerts
|

stx2vha Is the Dominant Genotype of Shiga Toxin‐Producing Escherichia coli O157:H7 Isolated from Patients and Domestic Animals in Three Regions of China

Abstract: Shiga toxin‐producing Escherichia coli (STEC) O157:H7 strains were isolated from domestic animals and patients from Xuzhou City, Jiangsu Province, China and the bordering Anhui and Henan Provinces and were examined for the stx genotype. Of 390 strains, 277 were identified as genotype stx2vha; 41, stx2; 51, stx2‐stx1; 1, stx2‐stx2vha‐stx1; 5, stx2‐stx2vha; and 15 were un‐typeable. Of the 277 stx2vha‐bearing isolates, 116 were isolated from goats; 42, cattle; 38, hens, and 35 from pigs. The study shows stx2vha i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…This serotype has been found to be responsible for a wide range of illnesses in humans, including hemorrhagic colitis and hemolytic uremic syndrome. Although cattle have long been considered the principal reservoir of E. coli O157:H7, other domestic animals and their carcasses contain this microorganism (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…This serotype has been found to be responsible for a wide range of illnesses in humans, including hemorrhagic colitis and hemolytic uremic syndrome. Although cattle have long been considered the principal reservoir of E. coli O157:H7, other domestic animals and their carcasses contain this microorganism (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Cattle are considered to be the major reservoir of E. coli O157:H7 (Baker et al, 2007;Wang et al, 2008;Williams et al, 2008). Recent studies have also demonstrated that, conventional pigs were permissive host for E. coli O157:H7 (Booher et al, 2002;Cornick and Helgerson, 2004), though the prevalence of the organism in these studies was generally low, except for the results from Chile and Chinese Mainland and both suggested that, pig might be an important source of this organism in some countries (Borie et al, 1997;Zheng et al, 2005). Also, one family outbreak had been specifically traced back to pork salami and the E. coli O157 isolates from the couple and the salami carried stx 1 , stx 2 and eae genes and shared the same PFGE pattern (Conedera et al, 2007).…”
Section: Introductionmentioning
confidence: 54%
“…But the most important factor is stx2 (Osawa et al, 2000;Kawano et al, 2008). The STEC O157:H7 strains have been reported to produce stx 1 , stx 2, and stx 2c (Schmitt et al, 1991;Tyler et al, 1991;Osawa et al, 2000;Zheng et al, 2005;Kawano et al, 2008), while other stx 2 variants were often observed from non-O157:H7 STEC. However, the stx 2 gene can be interruptted by a 1310 bp insertion sequence IS1203 variant (IS1203v) which is inserted in the region encoding the amino-terminus of the B subunit with a duplication of 3 bp at the target site and is not cytotoxic to Vero cells (Kusumoto et al, 1999;Jinneman et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations